Studying Part-Time at University: From Research to Policy to Practice - Keast, David A. (Canadian Journal of Higher Education, 2000)
In the last few years universities in Canada have seen a noticeable decline in part-time enrollments. This trend has given rise to a number of pressing concerns regarding the needs and aspirations of part-time students and the status and future of part-time study. Unfortunately, these concerns exist against a backdrop of relatively little research on part- time university students, programs, and attendance which is useful for decisions on policy and practice. This paper highlights the results of research which examined part-time programming at Canadian universities and the needs and characteristics of undergraduate student populations with potential for part-time degree completion. It is argued that the mature, working, part-time learner constitutes a distinct nontraditional group, with a distinct set of educational needs and expectations. The findings suggest changes which may be necessary in university functioning in order to better serve these student populations in the future. Results are compared with other recent research and implications for institutional policy and practice are discussed.